Taxonomic studies on Idiocerini Leafhoppers (Hemiptera: Cicadellidae: Eurymelinae: Idiocerini) of Sri Lanka - Gnaneswaran, R. (Idiocerini Leafhoppers of Sri Lanka, 2021)
Seven species of Leafhoppers belong to the tribe: Idiocerini of Subfamily Eurymelinae in Family Cicadellidae, are reported from Sri Lanka based on the field study. Four species of Idioscopus, and each one species of genera Amritotus, Busoniomimus and Jogocerus were described with their distribution in the country. Busoniomimus manjunathi Viraktamath and Viraktamath and Jogocerus freytagi were described for the first time from Sri Lanka.
Keywords: Idiocerini; Busoniomimus; Jogocerus; Idioscopus